Impact of a one-stop rapid access venous ulcer clinic on inpatient admissions. (June 2023) - CR, Keohane; M, Alagha; MP, O'Shaughnessy; DP, Joyce; W, Tawfick; MA, Tubassam; SR, Walsh
Objectives: Venous leg ulcers (VLU) are prevalent and require a large investment of resources to manage. We investigated whether the introduction of a rapid access see-and-treat clinic for VLU patients affected rates of unplanned inpatient admissions with VLU. Methods: The Hospital Inpatient Enquiry database was consulted for data on admission rates, length of stay, bed-days used, and costs, across a 4-year period; 2 years since the introduction of the clinic, and the 2 years prior as a control. Results: Two hundred and eighteen patients admitted with VLU accounted for 2, 529 inpatient bed-days, 4.5 (2–6) admissions per month, and a median hospital stay of 7 (4–13) days across the study period. Median admissions decreased from 6 (2.5–8.5) per month before, to 3.5 (2–5) after introduction of the clinic ( p = 0.04). Bed-day usage fell from 62.5 (27–92.5), to 36.5 (21–44) days per month ( p = 0.035). Conclusions: Admissions and bed-day usage for inpatient management of VLU fell after commencing a one-stop, rapid access clinic.